Assessing the vulnerability of habitats through plant rarity patterns in the Pyrenean range. Issue 4 (10th March 2022) - Miranda Cebrián, Héctor; Font, Xavier; Roquet, Cristina; Pizarro Gavilán, Manuel; García, María Begoña
Abstract: Biodiversity is being severely affected by global change worldwide, but consequences differ across individual species and environments. Since rarity is a condition associated with vulnerability and extinction risk, it is a concerning factor itself that can also amplify the detrimental impact of global change drivers. Here, we assess differences in vulnerability derived from species rarity across environments in a South European mountain range, the Pyrenees, a complex landscape sheltering more than 3400 vascular plants. We first analyzed patterns of alpha taxonomic (richness) and phylogenetic diversity (standardized phylogenetic diversity, sesPD) from more than 18, 000 plant surveys across 14 different habitats to find out which ones shelter the highest diversity. Then, we classified plant species according to four criteria of rarity (Pyrenean endemic, regional geographic range, ecological specialization and local abundance) and estimated their frequency among habitats and their contribution to PD. Generalized linear models were used to compare richness and sesPD among habitats, and the relationship between each diversity metric and rare species proportion was assessed. Grasslands harbor the greatest number of species but are poor in sesPD, while inland surface waters contain fewer species but are the most phylogenetically diverse. Deciduous, evergreen and Mediterranean forests show both high species richness and sesPD. Rare species account for half of the regional species pool, and are more abundant in habitats with fewer species and higher sesPD. Diversity metrics showed opposite tendencies between them and with rare species proportion, emphasizing that they are not interchangeable. Our results highlight the vulnerability of rocky and water‐related habitats due to the rarity of the species they shelter, but only the latter match other assessments of habitat vulnerability to global change drivers. The analysis of rarity patterns can guide conservation efforts by identifying priority targets when information about direct threats to habitats is scarce or incomplete. Abstract : In this study, we explore the patterns of two aspects of diversity in the Pyrenean flora and use its rarity components as a proxy for habitat vulnerability. Wetlands and rocky habitats were considered the most vulnerable to biodiversity loss due to their low species richness, high phylogenetic diversity and higher incidences of rare species. This was consistent with other approaches to vulnerability in European habitats.